Multiprotocol routing for automatic remote meter reading using power line carrier systems. - Newbury, J. (IEEE Transactions on power delivery)
This paper addresses the potential applications of multi-protocol routing for automatic remote meter reading (ARMR). The paper concentrates on the special needs for these applications over the lower line, in terms of: the data on a lower line medium; transmitting and receiving data from any point on the low voltage distribution network; achieving reliable communications from any point on the low voltage distribution network to any other internal and external point; and the ability to increase system performance. Other communications media such as radio and telephone line are not ignored. The intention is to seek out a protocol or multiprotocol routing architecture, which could be used for power line carrier systems but equally could also he applied to these other media for the communication of metering data, and other services